"YouTube™ as a source of information on placenta accreta: A quality analysis". (May 2022) - Collà Ruvolo, Claudia; Califano, Gianluigi; Tuccillo, Alessandra; Tolentino, Sara; Cancelliere, Elena; Di Bello, Francesco; Celentano, Giuseppe; Creta, Massimiliano; Longo, Nicola; Morra, Simone; Saccone, Gabriele
Abstract: Objective: To evaluate the quality of YouTube™ videos on placenta accreta and to investigate if they can be used as a reliable source of information. Methods: We queried YouTube™ with terms related to placenta accreta. Patient Education Materials Assessment Tool for audio-visual content (PEMAT A/V), Global Quality Score (GQS), DISCERN score and Misinformation tool were used to assess videos' quality content. Results: Sixty-four videos were suitable for the analyses. Of those, 42 (65.6%) and 22 (34.4%) were produces by healthcare works and others, respectively. The median PEMAT A/V Understandability and Actionability score was 75 and 66.7%, respectively. According to GQS, 31.2 and 45.3% videos were excellent or good and generally poor or poor, respectively. The median DISCERN score of section 1 was 27 (out of 40), of section 2 was 16 (out of 35) and of section 3 was 2 (out of 5). According to Misinformation tool, the worst described aspect was the one regarding the possible risk factor associated to placenta accreta. Performing the quality assessment according to video authoring entity, videos produced by healthcare workers harbored a higher quality content, relative to the others. Conclusions: Currently, the overall consideration of YouTube™ video content on placenta accreta is low. Societies should invest new sources in producing higher quality videos to provide a helpful tool for physician during the counselling with patients.